Coupling of Finite Element and Boundary Element Methods for Structural Analysis of Shear Wall - Frame Building - Made Suarjana; Ari Wibowo (Jurnal Teknik Sipil, 2010)
Abstract. In this study a method to couple the finite element method (FEM) and the boundary element method (BEM) for solving structural analysis problems is investigated and implemented. The investigation is focused on developing and selecting a practical method for integrating the system of linear equations derived from the FEM and the BEM into a combined global system, and to study the efficiency and accuracy of the coupled method. A coupling method that based on transforming the system of equation from the BEM into a form that can be assembled to the global system of equation of the FEM is implemented. The coupled method is useful for solving structural analysis problem of shear wall-frame building. Shear walls are modeled as plane stress BEM regions, while frames are modeled as beam-column FEM regions. The accuracy and efficiency of the coupled method is studied by solving structural analysis problems of an 8 stories shear wall-frame building model. The coupled FEM and BEM method has been implemented for structural analysis of shear wall-frame building in a personal computer program. The coupled method is much more complicated to implement compared to the FEM. However, the benefit of reduced complexity in mesh generation and increased efficiency in both memory requirement and computing time can be very significant.Abstrak. Pada studi ini diteliti metode untuk menggabungkan metode elemen hingga (FEM) dengan metode elemen batas (BEM) dalam menyelesaikan masalah-masalah analisis struktur. Fokus penelitian adalah mengembangkan dan memilih metode yang praktis untuk menggabungkan sistem persamaan linier yang diturunkan dari FEM dan BEM menjadi satu sistem persamaan global, dan untuk mempelajari efisiensi dan akurasi dari metode gabungan. Metode penggabungan yang diterapkan pada dasarnya mentransformasikan sistem persamaan BEM menjadi bentuk yang dapat dirakit ke sistem persamaan global FEM. Sistem gabungan dipergunakan untuk menyelesaikan masalah analisis struktur gedung dengan sistem struktur portal dan dinding geser. Dinding geser dimodelkan dengan BEM plane stress, sedangkan portal dimodelkan dengan FEM balok-kolom. Metode gabungan diterapkan menjadi program komputer. Akurasi dan efisiensi metode gabungan dipelajari dengan menyelesaikan analisis struktur gedung 8 lantai dengan sistem portal-dinding geser. Sistem gabungan lebih rumit dalam proses pemrogramannya, tetapi keuntungan diperoleh dari kemudahan pembuatan model struktur dan peningkatan efisiensi dalam pemakaian memori komputer dan waktu penyelesaian.